An analysis of the composition of gain and growth of primal cuts of Iberian pigs of 10 to 150 kg body weight as affected by the level of feeding and dietary protein concentration - Nieto, Rosa; Lara, Luis; Barea, Roberto; García-Valverde, Rosa; Conde-Aguilera, Jose A.; Aguilera Sánchez, Jose F. (Spanish Journal of Agricultural Research, 2014)
A meta-analysis was made of data from a total of 211 growing-finishing Iberian (IB) pigs from four separate and independent sets of trials. Within each set of trials, a factorial arrangement of treatments was used, involving several concentrations of ideal protein in the diets and two or three levels of feed intake. Pigs were slaughtered at several stages of growth from 10 to 150 kg body weight (BW). The partition of dietary protein in the body of the pigs, the empty-body gain (EBG), the chemical composition of EBG, growth of primal cuts in the cold eviscerated carcass (without head, feet, and tail), and mass of dissected tissues in trimmed shoulder and ham were determined. Linear regression equations allowed estimating N requirements for maintenance as 175 mg/(kg BW0.75 · kg dry-matter intake) · d-1 and an average value for the net efficiency of utilization of the dietary protein apparently absorbed of 0.386. In pigs offered adequate protein to energy diets, EBG was predicted as a function of average BW and feeding level (p<0.001). Multiple regression equations were constructed, which derived nutrient (g kg-1) or energy (MJ kg-1) composition of EBG as a function of empty-body weight (EBW), dietary protein to energy ratio, and level of feeding (p<0.001). These predictive equations, not applicable to pigs of lean and conventional genotypes, can contribute to the design of optimal feeding strategies to improve the efficiency of IB pig production systems and to achieve high quality standards in end products for the market.